UJI DOSIS FUNGISIDA BERBAHAN AKTIF PROPINEB DAN WAKTU APLIKASI TERHADAP PERTUMBUHAN (Fusarium oxysporum) SECARA IN VITRO - Nurhasanah; Sulhaswardi (DINAMIKA PERTANIAN, 2021)
The aim of this study was to determine the effect of administering a fungicide with the active ingredient propined and the time of application on the growth of Fusarium oxysporum in vitro. The design used in this study was a factorial Completely Randomized Design (CRD) using two factors, the first factor was the dose of fungicide which consisted of 3 levels (F), namely: 700 ppm, 1700 g/l water, and 2.7 g/l water. and the second factor was the time of inoculation which consisted of three levels so that there were 9 treatment combinations with 3 replications, so there were 27 experimental units. Each experimental unit consisted of 2 Petri dish plates which were inoculated and sampled so that there were 54 Petri dish plates. Parameters observed were the effective day of colony formation, colony diameter, conidia length of Fusarium oxysporum, inhibition of growth of Fusarium oxysporum, and macroscopic and microscopic identification of Fusarium oxysporum. If the calculated F is greater than the F table, then the BNJ test is continued at the 5% level. Based on the results of the study, the following can be concluded: treatment interaction with propined concentration and application time affects all observation parameters, where the best treatment is propined concentration of 2700 ppm and concurrent application of propined (F3S2). The main effect of real propined concentration on all observation parameters, the best treatment was propined concentration of 2700 ppm (F3). The main effect of actual application time on all observational parameters, the best treatment was with a propined application (S2).